The art of simple food II - Waters, Alice (Clarkson Potter/Publishers, 2013)
"For the hundreds of thousands of readers who bought Alice Waters's bestselling and now-classic book The Art of Simple Food, and for supporters of all ages of the sustainable food movement, here is a timely cookbook that centers on Alice's plant-forward way of cooking and puts forth her passion for seasonality and celebrating all vegetables. Alice Waters is the leader of the local, sustainable food movement. While The Art of Simple Food was steeped in general cooking technique, The Art of Simple Food II brings vegetable-forward meals to the table. With 300 seasonal recipes and 300 exquisite line drawings, this follow-up to the revered Art of Simple Food beautifully encompasses Alice's vision for eating what grows in our earth, all year long. This book is for longtime fans of Alice plus the new generation of home cooks who care deeply about the source of their food and who so admire Alice's efforts in the food movement. It is a must-read for home cooks who shop at farmer's markets and supermarket perimeters, and who belong to CSAs, as she guides you on how to choose the best ingredients. And it will be of special interest to those who grow their own food in their kitchens, backyards, or community gardens because gardening information is included. Alice teaches you how to bring the most flavor and versatility to the plants, using familiar and new ingredients. With this book, she empowers you to nourish yourself for a more responsible and rewarding life in the kitchen and at the table"--